Effect of feeding non-conventional tree fodders on fatty acid composition and nitrogen fractions of goat milk - KOUSHKI, M R; GUPTA, M P; OGRA, J L (The Indian Journal of Animal Sciences, 2013)
Feeding of non-conventional tree forages, viz. Leucaena teucocephala (LL), Dichrosles nutan (DN), Capparis horrida (CH),Balaniles aegypliaca (BA), did not aller the levels of butyric and capric acids in goat milk-fat. Feeding of LL and BA caused an appreciable increase in caprylic and capric acids, respectively,in milk of both Jamunapari and Barbari goats. Myristic and palmitic acids also increased when nonconventional forages were fed. These feeds had in general depressed sLearic acid content. Feeding of DN had similar effect as thai of control. Unsaturated fally acids were also influenced by feeding of nonconventionalroughages. Breed variation had insignificant effet on the constituent fatty acids of goat milk. Total N, non-protein N (NPN), protein N and casein N contents of goat milk were significantly affected by the feeding of non-conventional forages. BTeed variation only had significant effect on NPN content of goat milk. The effect of fceding regimes and breed variation was nonsignificant on whey protein, N,total albumin N, B-Iactoglobulin N, residual albumin N, proteose peptone N and globulin N in goat milk.